What is an exponent?

Powers are the number that is multiplied by itself several times.
Each power consists of two main parts: 

  • Base of the power: The number that fulfills the requirement of duplication. The principal number is written in large size.
  • Exponent: the number that determines how many times the power base needs to be multiplied by itself.
    The exponent is written in small size and appears on the right side above the power base.
A - How we will identify the exponent

Practice Exponents Rules

Examples with solutions for Exponents Rules

Exercise #1

8132= \frac{81}{3^2}=

Video Solution

Step-by-Step Solution

First, we recognize that 81 is a power of the number 3, which means that:

34=81 3^4=81 We replace in the problem:

8132=3432 \frac{81}{3^2}=\frac{3^4}{3^2} Keep in mind that the numerator and denominator of the fraction have terms with the same base, therefore we use the property of powers to divide between terms with the same base:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n} We apply it in the problem:

3432=342=32 \frac{3^4}{3^2}=3^{4-2}=3^2 Therefore, the correct answer is option b.

Answer

32 3^2

Exercise #2

192=? 19^{-2}=\text{?}

Video Solution

Step-by-Step Solution

In order to solve the exercise, we use the negative exponent rule.

an=1an a^{-n}=\frac{1}{a^n}

We apply the rule to the given exercise:

192=1192 19^{-2}=\frac{1}{19^2}

We can then continue and calculate the exponent.

1192=1361 \frac{1}{19^2}=\frac{1}{361}

Answer

1361 \frac{1}{361}

Exercise #3

2423= \frac{2^4}{2^3}=

Video Solution

Step-by-Step Solution

Let's keep in mind that the numerator and denominator of the fraction have terms with the same base, therefore we use the property of powers to divide between terms with the same base:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n} We apply it in the problem:

2423=243=21 \frac{2^4}{2^3}=2^{4-3}=2^1 Remember that any number raised to the 1st power is equal to the number itself, meaning that:

b1=b b^1=b Therefore, in the problem we obtain:

21=2 2^1=2 Therefore, the correct answer is option a.

Answer

2 2

Exercise #4

9993= \frac{9^9}{9^3}=

Video Solution

Step-by-Step Solution

Note that in the fraction and its denominator, there are terms with the same base, so we will use the law of exponents for division between terms with the same base:

bmbn=bmn \frac{b^m}{b^n}=b^{m-n} Let's apply it to the problem:

9993=993=96 \frac{9^9}{9^3}=9^{9-3}=9^6 Therefore, the correct answer is b.

Answer

96 9^6

Exercise #5

(4274)2= (\frac{4^2}{7^4})^2=

Video Solution

Step-by-Step Solution

(4274)2=42×274×2=4478 (\frac{4^2}{7^4})^2=\frac{4^{2\times2}}{7^{4\times2}}=\frac{4^4}{7^8}

Answer

4478 \frac{4^4}{7^8}

Exercise #6

1123=? \frac{1}{12^3}=\text{?}

Video Solution

Step-by-Step Solution

To begin with, we must remind ourselves of the Negative Exponent rule:

an=1an a^{-n}=\frac{1}{a^n} We apply it to the given expression :

1123=123 \frac{1}{12^3}=12^{-3} Therefore, the correct answer is option A.

Answer

123 12^{-3}

Exercise #7

(43)2= (4^3)^2=

Step-by-Step Solution

To solve (43)2 (4^3)^2 , we use the power of a power rule which states that (am)n=amn (a^m)^n = a^{m \cdot n} .

Here, a=4 a = 4 , m=3 m = 3 , and n=2 n = 2 .

So, we calculate 432 4^{3 \cdot 2} ,

which simplifies to 46 4^6 .

Answer

46 4^6

Exercise #8

(35)4= (3^5)^4=

Video Solution

Step-by-Step Solution

To solve the exercise we use the power property:(an)m=anm (a^n)^m=a^{n\cdot m}

We use the property with our exercise and solve:

(35)4=35×4=320 (3^5)^4=3^{5\times4}=3^{20}

Answer

320 3^{20}

Exercise #9

(23)6= (2^3)^6 =

Step-by-Step Solution

To solve the given expression (23)6 (2^3)^6 , we apply the power of a power rule (am)n=amn (a^m)^n = a^{m \cdot n} . Here, a=2 a = 2 , m=3 m = 3 , and n=6 n = 6 .

Thus, we calculate the exponent:

36=18 3 \cdot 6 = 18

So, (23)6=218 (2^3)^6 = 2^{18} .

Answer

218 2^{18}

Exercise #10

(2×7×5)3= (2\times7\times5)^3=

Video Solution

Step-by-Step Solution

To solve the problem, we need to apply the power of a product exponent rule. This rule states that when you raise a product to a power, it's the same as raising each factor to that power. In mathematical terms, if you have (abc)n (abc)^n , it is equivalent to an×bn×cn a^n \times b^n \times c^n .

Let's apply this rule step by step:

Our original expression is: (2×7×5)3 (2 \times 7 \times 5)^3 .

We first identify the factors inside the parentheses as 2 2 , 7 7 , and 5 5 .

According to the Power of a Product rule, we can distribute the exponent3 3 to each factor:

First, raise 2 2 to the power of 3 3 to get 23 2^3 .

Then, raise 7 7 to the power of 3 3 to get 73 7^3 .

Finally, raise 5 5 to the power of 3 3 to get 53 5^3 .

Therefore, the expression (2×7×5)3 (2 \times 7 \times 5)^3 simplifies to 23×73×53 2^3 \times 7^3 \times 5^3 .

Answer

23×73×53 2^3\times7^3\times5^3

Exercise #11

54×25= 5^4\times25=

Video Solution

Step-by-Step Solution

To solve this exercise, first we note that 25 is the result of a power and we reduce it to a common base of 5.

25=5 \sqrt{25}=5 25=52 25=5^2 Now, we go back to the initial exercise and solve by adding the powers according to the formula:

an×am=an+m a^n\times a^m=a^{n+m}

54×25=54×52=54+2=56 5^4\times25=5^4\times5^2=5^{4+2}=5^6

Answer

56 5^6

Exercise #12

3532= \frac{3^5}{3^2}=

Video Solution

Step-by-Step Solution

Using the quotient rule for exponents: aman=amn \frac{a^m}{a^n} = a^{m-n} .

Here, we have 3532=352 \frac{3^5}{3^2} = 3^{5-2}

Simplifying, we get 33 3^3

Answer

33 3^3

Exercise #13

5654= \frac{5^6}{5^4}=

Video Solution

Step-by-Step Solution

Using the quotient rule for exponents: aman=amn \frac{a^m}{a^n} = a^{m-n} .

Here, we have 5654=564 \frac{5^6}{5^4} = 5^{6-4} . Simplifying, we get 52 5^2 .

Answer

52 5^2

Exercise #14

724=? 7^{-24}=\text{?}

Video Solution

Step-by-Step Solution

Using the rules of negative exponents: how to raise a number to a negative exponent:

an=1an a^{-n}=\frac{1}{a^n} We apply it to the problem:

724=1724 7^{-24}=\frac{1}{7^{24}} Therefore, the correct answer is option D.

Answer

1724 \frac{1}{7^{24}}

Exercise #15

41=? 4^{-1}=\text{?}

Video Solution

Step-by-Step Solution

We begin by using the power rule of negative exponents.

an=1an a^{-n}=\frac{1}{a^n} We then apply it to the problem:

41=141=14 4^{-1}=\frac{1}{4^1}=\frac{1}{4} We can therefore deduce that the correct answer is option B.

Answer

14 \frac{1}{4}